Introduction to Alienation Theory and Research in Education and Social Work - Dirk Michel-Schertges; Henrik Skovlund (Social Work and Society, 2019)
During the past decades in social science,"critical thinking" appeared mainly embedded in theoretical conceptions and research focusing on social inequality and viabilities in social mobility rather than on immanent social critique. Thus, it followed, inter alia, either the premises of"objective sciences", or the"postmodern" understanding of cultural relativism. However, after the continuing global financial and ecological crisis, questions of state sovereignty and the distribution of income and wealth are back on the agenda. In order to create truly participatory and democratic societies, seemingly forgotten concepts of social critique seem necessary to reveal the irrationalities of contemporary Western society, particularly its hidden oppressive social structures. Among such concepts, we find the notion of"alienation", a concept that on a broad scale offers approaches in order to understand oppressing and irrational structures of society governing the lifestyle, desires, goals, social position and social relations of the individual. Such issues are of importance regarding politics, social control, marginalization, discrimination as well as the general health and wellbeing of the citizens of Western societies, especially because the values from which people struggle to make sense of everyday life may counteract those of economic growth. After being deemphasized for several decades, alienation theories and research need to re-emerge from a long-lasting sleep. The special issue at hand is exactly such an attempt to revive alienation theory by demonstrating how it can be applied to social work on many levels: From the history of the overall structures of society, through educational policies, to the"man on the floor". Among the latter, we find those groups of citizens who end up in marginalized positions that seemingly are closely related to alienation from the mainstream society and eventually themselves when alienation reaches its extremes in form of mental sufferings. The main body of articles take departure in the Scandinavian welfare regime in general, and the Danish state in particular, since the latter represents a typical example of a Western democracy, which on one the hand are guided by basic ideals of citizen's"welfare" and on the other hand are equally guided by global and national goals of economic growth. Within this framework, alienation theory is contested with various contemporary social appearances and phenomena related to knowledge-based organization, institutionalization, agents and recipients of social policies.